Disease Knowledge, Illness Perceptions, and Quality of Life in Adolescents With Sickle Cell Disease: Is There a Link?. (3rd November 2017) - Asnani, Monika Rani; Barton-Gooden, Antoinette; Grindley, Marlyn; Knight-Madden, Jennifer
Disease knowledge, illness perceptions, and quality of life (QOL) were examined in 150 adolescents (mean age = 16.1 years, SD = 1.9; 49.3% males) with sickle cell disease (SCD). Females had higher knowledge ( P = .004), lower QOL ( P = .02), and perceived their illness to be more unpredictable ( P = .03). Those with more severe disease perceived their illness to be unpredictable with worse outcomes. Those with higher knowledge scores perceived their illness to be chronic, made more sense of their illness, and perceived greater personal and treatment control. Final hierarchical regression model showed that secondary education as compared to primary education level ( P < .001) was positively correlated whereas disease severity ( P < .001), perceived unpredictability ( P = .024), and negative emotions ( P < .001) were negatively correlated with QOL. Health practitioners should assess adolescents' illness perceptions and encouraging continuing schooling and addressing emotional/psychological problems could improve their QOL.